2018
DOI: 10.14740/jocmr3375w
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Reporting System Use During Handoffs Reduces Patient Length of Stay in the Emergency Department

Abstract: BackgroundEmergency department (ED) shift handoffs are potential sources of delay in care. We aimed to determine the impact that using standardized reporting tool and process may have on throughput metrics for patients undergoing a transition of care at shift change.MethodsWe performed a prospective, pre- and post-intervention quality improvement study from September 1 to November 30, 2015. A handoff procedure intervention, including a mandatory workshop and personnel training on a standard reporting system te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…[5,6] Other standardized approaches using computerized or electronic handoff tools have also been suggested and utilized. [7,8] The ANC process included a standardized admission template that utilized a secure, electronic texting system. This standardized template served the dual purpose of clearly signaling the beginning of the admissions process, providing consistent information to the inpatient team, and allowing the ANC to simultaneously begin locating an appropriate bed for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5,6] Other standardized approaches using computerized or electronic handoff tools have also been suggested and utilized. [7,8] The ANC process included a standardized admission template that utilized a secure, electronic texting system. This standardized template served the dual purpose of clearly signaling the beginning of the admissions process, providing consistent information to the inpatient team, and allowing the ANC to simultaneously begin locating an appropriate bed for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Dahlquist et al demonstrated a statistically significant reduction in ED length-of-stay from 311minutes to 263 minutes (p < .05). [8] Additionally, direct, rather than consultative admission models have been shown to be more efficient with regards to ED turnaround times. [14] The ANC admission process showed similar gains in process efficiency and patient flow, as the time-to-departure for patients admitted to an inpatient medical team was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabei können beispielsweise verbesserte Arbeitsprozesse im Zusammenhang mit Schichtwechseln und Übergaben transparenter und effizienter gestaltet werden. Dies kann unter anderem durch standardisierte Berichtssysteme und strukturierte Übergaben erfolgen, um den Verlust von Informationen zu verhindern sowie die Effizienz der Behandlung zu verbessern [42]. Zudem muss die Wertschätzung und Zusammenarbeit, Integration und Koordination der Teamarbeit zwischen den einzelnen Einrichtungen gestärkt sowie die gerechte Fehlerkultur implementiert und mittels Schulungskonzepten trainiert werden [43].…”
Section: Erhebungsinstrumenteunclassified
“…This results in ED overcrowding, increasing the chances of medical errors, patient wait times, patient length of stay, and mortality. Similarly, handoffs also increase the chances of medical errors, length of stay and have other negative impacts on patient safety (Dahlquist et al 2018;Maughan et al 2011). Although researchers have focused on addressing the negative impact of overcrowding on patient safety, very few have focused on addressing the impact of ED handoffs on patient safety.…”
Section: Introductionmentioning
confidence: 99%